Occupational Engagement and Positive Psychological Measures in Two Collectivistic Cultures. (December 2020) - Vuyk, M. Alexandra; Lei, Yujia; Krieshok, Thomas S.; Codas, Gerónimo
This study assessed occupational engagement and its relationship to positive psychological measures in two collectivistic cultures. Undergraduate students in China ( n = 230) and Paraguay ( n = 231) completed the Occupational Engagement Scale for Students (OES-S), a one-factor, 9-item scale to measure occupational engagement, the Vocational Identity Scale, the Satisfaction With Life Scale, the Adult Hope Scale, and the Personal Growth Initiative Scale-II. Multigroup confirmatory factor analyses with OES-S scores were held for partial strong measurement invariance. OES-S scores correlated with scores on positive psychological measures. While the OES-S has room for improvement, occupational engagement seems to be a viable cross-cultural construct applicable to collectivistic cultures.